LOBBYING IN LITHUANIA AND ABROAD: THE PROBLEMS OF LEGAL REGULATION ANDINSTITUTIONALIZATION - Lukošaitis, Alvidas (Politologija, 2015)
This article presents analysis and typological classification of legal regulation of lobbying in other countries and looks for the reasons of failure to legitimize lobbying activities in Lithuania which would serve as important preventive measure against corruption. It discusses the reasons why lobbying regulation is usually ineffective. The reasons why regulation is often ineffective (dependant variable) are determined by examining the gaps in or breaches of legal regulation, the peculiarities of the political procedures within the governmental system and the degree of acceptance within the socio-cultural context to the practice of lobbying (independent variables). The research is based on three assumptions: First: further development of legal regulation of lobbying is meagerly correlated to the realities of political processes and therefore inconsistent, the decisions taken often lack genuine broad-based political will. Second: specific political processes derived from the Lithuanian political system do not offer equal conditions for the activities of interest groups, and that is an unfavorable factor for the institutionalization of lobbying. Third: features of socio-cultural context may create a favorable environment for corrupt methods of influencing political decisions.An analysis of foreign practice shows that the effectiveness of legal regulation is determined by a number of factors. Concrete lawmaking decisions determine the variety of models (regimes) of legal regulation in different countries, but their classification is quite complex. Certain countries of Anglo-Saxon tradition (e.g. the USA and Canada) have mature traditions of lobbying activities. Regulation there is comparatively comprehensive. Continental Europe can be divided into “old Europe” and Central-Eastern (post-Soviet) Europe. In the latter, traditions of lobbying activities are practically non-existent and every attempt at legitimization of lobbyism is met with negative reaction by the society and interest groups. The passed legal acts often lack genuine legitimacy.In Lithuania, institutionalization of legitimate lobbying faces problems of effectiveness of legal regulation, of integrity and of the legitimacy of legal regulations. Legal norms about regulations are in a way “frozen” – not well correlated to the relevance and understanding of political processes nor their effects and implementation challenges having been revealed in the process of implementation of the Law on Lobbyism of the Republic of Lithuania. For example, the legal regulation does not cover the local government level. The functions of interest groups – not only representation but influencing political decisions – are not taken into account, the problems of indirect lobbyism (financing of political parties and electoral campaigns) are not properly emphasized. Regulation should cover not only the lawmaking process but other decisions of public administration as well, perhaps most importantly, at the local government level.The principles of Lithuanian political system (the model of interaction of governmental institutions, the rules of election of representative government, the features of party system etc.) have determined certain specifics of political process which are fragmented in Lithuania. There are many different political and institutional players. The structural complexity of political processes complicates the activities of interest groups and the strategies they might choose to employ to influence the actions of governments at all levels. Because of the lack of resources and appreciation by society, their goals are difficult to attain. Thus incentives are created for interest groups to act “in camera” (not publicly), to influence political processes by employing illegitimate methods. This can turn any public policy into a private one. The “political nets” of interest groups are often characterized by the traditions of reticence, privileged status and special interests. This all suggests that the environment for the regulation of lobbying is not currently favorable.The interrelationships of the interest groups acting in policy making and the state are difficult to define. Undoubtedly some structural and functional segments of corporatism and cultural relics of clientelism, e.g. nepotism etc., still play a significant role in the political culture of Lithuania that shape the contents and the direction of political process and the behavior of the “players”. Some authors assert that such highly indefinable relations between the state and interest groups and the powers of objects acting in political process may be called a “sort of hybrid” – between chaotic pluralism, sectoral corporatism and strains of mutant clientelism. The challenge of regulating lobbying under such conditions is a difficult task.Civic society is weak in Lithuania, and many citizens know little about the importance of legal means aimed at influencing governmental institutions. These factors encourage tolerance of corrupt behavior and the use of illicit methods to influence political decisions. The socio-cultural standards inherited from the Soviet system have conditioned the corrupt societal mentality that in political process is manifested in a variety of corporate corruption (guidance by narrow interests, clientelism, illicit lobbyism etc.).Lithuanian indices of societal associativeness and civic power do not ensure the control of political power. They are too weakly acted upon to make the authorities act as the democratic system requires – publicly, transparently, and responsibly. Research data show the rate of corruption is high. Society is largely indifferent to illicit methods of influence because of the lack of faith in the government that is perceived to serve narrow interest groups instead of the interests of the larger society. Such socio-cultural context, often characterized by the conflict between democratic values and soviet relics, is also not favorable to effective regulation of lobbying. The currently available means of legal regulation are not commensurate with the current expectations of political culture. The potential legal norms are denied and become a mere declaration.In summary, the current institutional, socio-cultural and legal regulative factors are not favorable to regulation of lobbying in Lithuania. That, however, should not mean that there should be no effort to implement effective, fair and democratic regulations on the process. A necessary precursor to such implementation may well require further cultural indoctrination. It may require the establishment of democratic institutions first. With those in place, then respective valued can be formed. This will then engender the creation of adequate values, a changed political culture that will understand and support the operation of these institutions and the future democratic behavior of civic society and interest groups.